Seismic Hazards Implications of Uplifted Pleistocene Coral Terraces in the Gulf of Aqaba - W. Bosworth (Nature Portfolio, 2017)
Abstract The Gulf of Aqaba transform plate boundary is a source of destructive teleseismic earthquakes. Seismicity is concentrated in the central sub-basin and decreases to both the north and south. Although principally a strike-slip plate boundary, the faulted margins of the Gulf display largely dip-slip extensional movement and accompanying footwall uplift. We have constrained rates of this uplift by measurements of elevated Pleistocene coral terraces. In particular the terrace that formed during the last interglacial (~125 ka) is found discontinuously along the length of the Gulf at elevations of 3 to 26 m. Global sea level was ~7 m higher than today at 125 ka indicating net maximum tectonic uplift of ~19 m with an average rate of ~0.015 cm/yr. Uplift has been greatest adjacent to the central sub-basin and like the seismicity decreases to the north and south. We suggest that the present pattern of a seismically active central region linked to more aseismic areas in the north and south has therefore persisted for at least the past 125 kyr. Consequently the potential for future destructive earthquakes in the central Gulf is greater than in the sub-basins to the north and south.